(untitled) (KULT_online, 2015)
In her dissertation, published in 2013, Yvonne Robel explores the controversy surrounding the genocides on Herero and Nama, on Armenians as well as on Sinti and Roma, which have become a "matter of debate" (Verhandlungssache) since the 1990s. The discourse-analytical approach marks the understanding of politics of history and memory and guides the focus beyond concrete political action towards discursive negotiations about norms of public speech and commemoration. Hereby, the study seeks to reconstruct the "order of discourse" and, in doing so, to show in which ways the historical-political debates have developed since the 1990s. The empirical findings emphasize to what extent the direction of memory of these three "newly discovered" genocides is mainly a question of naming and recognition and that, currently, there are significant limitations on what can be said and remembered.